(untitled) (Journal of Engineering, 2021)
Experimental measurements were done for characterizing current-voltage and power-voltage of two types of photovoltaic (PV) solar modules; monocrystalline silicon (mc-Si) and copper indium gallium di-selenide (CIGS). The conversion efficiency depends on many factors, such as irradiation and temperature. The assembling measures as a rule cause contrast in electrical boundaries, even in cells of a similar kind. Additionally, if the misfortunes because of cell associations in a module are considered, it is hard to track down two indistinguishable photovoltaic modules. This way, just the I-V, and P-V bends’ trial estimation permit knowing the electrical boundaries of a photovoltaic gadget with accuracy. This measure gives extremely significant data to the plan, establishment, and upkeep of PV frameworks. Three methods, simplified explicit, slope, and iterative, are used to compute two solar models’ parameters using MATLAB code. The percentage maximum power errors at (600 and 1000) W/m2 for both current-voltage and power-voltage values with the corresponding measured ones using the slope method are 0.5% and 3% for monocrystalline silicon copper indium gallium di-selenide, respectively. The iterative method is 5 % and 10% for monocrystalline silicon and copper indium gallium di-selenide. Finally, for the simplified explicit 8% and 9%, for monocrystalline silicon and copper indium gallium di-selenide, respectively. The slope method gives more close results with the corresponding measured values than the other two methods for the two PV solar modules used. Consequently, the slope method is less influenced by the meteorological condition.